Can CSF biomarkers predict future MS disease activity and severity?. (April 2020) - Magliozzi, Roberta; Cross, Anne H
Multiple sclerosis (MS) is a heterogeneous disease. With several disease modifying treatments of different mechanisms of action in use now and in development, it is important to identify reliable biomarkers to identify those higher risk MS patients in whom stronger but riskier treatments might be used, as well as to identify those for whom safer treatments of lower efficacy would be sufficient. Here we review cerebrospinal fluid (CSF) and blood biomarkers that show promise for differentiating people with MS who are at risk for severe disease and disability from those with more benign disease. We reviewed published literature for studies reporting biomarkers with predictive value in MS. Most studies of MS CSF found the presence of oligoclonal bands (both IgG and IgM), high IgG index and high levels of kappa light chains to each be associated with worse prognosis. Neurofilament light chain (NfL) and two markers of glial activation, glial fibrillary acidic protein (GFAP) and YKL-40, were higher in CSF of people with subsequent clinical progression or imaging evidence for neurodegeneration. Few reports have been made yet on the prognostic significance of blood NfL, but in one early report baseline, serum NfL (sNfL) predicted subsequent brain volume loss.